2004
DOI: 10.7863/jum.2004.23.8.1065
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Sonography of Intracranial Arteriovenous Malformations

Abstract: Our experience has indicated that a combination of sonographic imaging and color and spectral Doppler imaging improves surgical resection of such lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Many authors have described the intraoperative use of ultrasound with and without Doppler to help guide resection in the adult population, 2,4,6,8,10,12,20,[22][23][24]26,27,28 while others have shown the benefits of integrated neuronavigation. 1,14,22 Intraoperative angiography and indocyanine green video-angiography have also been used in conjunction with intraoperative Doppler ultrasound to aid AVM resection in the adult population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have described the intraoperative use of ultrasound with and without Doppler to help guide resection in the adult population, 2,4,6,8,10,12,20,[22][23][24]26,27,28 while others have shown the benefits of integrated neuronavigation. 1,14,22 Intraoperative angiography and indocyanine green video-angiography have also been used in conjunction with intraoperative Doppler ultrasound to aid AVM resection in the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have described ultrasound with and without intravenous contrast in AVM surgery in adults to aid resection, to check the extent of resection, and to increase overall surgical confidence. 4,6,8,10,24,26,28 Other authors have reported using neuronavigational software in conjunction with intraoperative ultrasound. 1,14,22 Intraoperative angiography or intraoperative indocyanine green video-angiography (ICGA) has also been used in conjunction with intraoperative Doppler ultrasound to aid AVM resection.…”
mentioning
confidence: 99%
“…As a noninvasive method, however, TCCS is very suitable for postoperative follow-up examinations and for postembolization monitoring, particularly if the AVM is located in the temporal or deep basal brain regions, as well as for intraoperative sonography. 27 The method can be regarded as a useful supplement to the palette of established noninvasive diagnostic techniques such as MRI and magnetic resonance angiography.…”
Section: A B Cmentioning
confidence: 99%
“…It is a valuable adjunct in the localization and excision of the AVM and has been used in AVM surgery. The value of intraoperative real-time ultrasound during surgery of AVMs has been investigated by many researchers [11,[30][31][32][33][34][35][36] . The niduses of AVM are localized and defined precisely by ultrasound due to their dichromatic flow pattern.…”
Section: Intraoperationmentioning
confidence: 99%